Numeracy students’ perspectives on a new digital learning tool at a South African university - Delport, D.H. (South African Journal of Higher Education, 2019)
Students thrive in learning environments in which they stay engaged, interested and motivated. MindTap Math Foundations, a digital learning tool, claims to bring elements from the interactive, gamified world to transform learning so that students stay engaged, persist through challenges, feel more supported and connected to instructors, other students, as well as their own learning experience. A South African university was the first higher education institution in South Africa to make use of this personalised learning system. A survey was employed to assess the effectiveness of MindTap Math Foundations as a digital learning tool. The focus of the article is on the analysis of the open-ended questions in the survey. The findings of this research support the claims Cengage make regarding the platform’s benefits. Participants’ responses revealed that the new digital learning tool is generally perceived as positive and beneficial for learning numeracy. Students’ feedback also provided ideas and proposals for potential enhancement. Through students’ experiences shared it was possible to pinpoint the strengths and challenges about aspects needing consideration and improvement.